Nietzsche's on the genealogy of morality : - May, Simon (Cambridge critical guides, 2011)
"This volume brings together a broad range of prominent philosophers writing in English, from both sides of the Atlantic and beyond, so giving a sense for the current state of English-speaking scholarship in the field. Most do not limit themselves to close textual exegesis, but rather treat fundamental themes and aims of the work as a whole, freely discussing their philosophical importance"--